Preadmission Functional Decline Predicts Functional Improvement Among Older Patients Admitted to Acute Care Hospital. (26th October 2017) - Gagliardi, Cristina; Corsonello, Andrea; Di Rosa, Mirko; Fabbietti, Paolo; Cherubini, Antonio; Mercante, Oriano; Mazzei, Bruno; Postacchini, Demetrio; Deales, Alberto; Bustacchini, Silvia; Lattanzio, Fabrizia
Abstract: Background: Functional decline from preadmission to admission may represent an important predictor of functional trajectories during hospitalization among older patients. Therefore, we aimed at describing the impact of preadmission decline on functional trajectories among older hospitalized patients. Methods: Our series consisted of 2, 011 patients aged 65 years or more consecutively admitted to four acute care wards of Geriatric Medicine participating to a multicenter observational study. Enrolled patients underwent comprehensive geriatric assessment (CGA) by Inter-RAI Minimum Data Set. Main outcomes were functional decline or improvement from hospital admission to discharge based on Activities of Daily Living (ADL) scale. The main exposure variable was ADL decline during the preadmission period (ie, 3 days before the onset of acute illness), and its impact on functional trajectories during stay was investigated by Cox regression models after adjusting for potential confounders. Results: After adjusting for potential confounders, preadmission functional decline was significantly associated with functional improvement during stay (hazard ratio [HR] = 6.65; 95% confidence interval [CI] = 5.01–8.84), but not with functional decline. Severe cognitive impairment (HR = 0.28, 95% CI = 0.13–0.60), visual impairment (HR = 0.60, 95% CI = 0.41–0.89), and weight loss (HR = 0.67, 95% CI = 0.47–0.94) were associated with functional improvement during stay. Hearing impairment (HR = 1.94, 95% CI = 1.17–3.23) and mild (HR = 2.54, 95% CI = 1.41–4.58) or severe cognitive impairment (HR = 2.72, 95% CI = 1.13–6.56) were associated with functional decline during stay. Conclusions: Patients experiencing recent preadmission functional decline should be considered as those for which the geriatric approach may lead to the better functional result in the acute care setting. CGA allows to individuate risk factors to be addressed in the acute care setting.